2003
DOI: 10.1038/sj.bjc.6600802
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression and altered processing of fibulin-1 protein in human breast cancer

Abstract: The extracellular matrix protein fibulin-1 suppresses the motility and invasiveness of a variety of tumour cell types in vitro as well as the growth of fibrosarcoma tumours in nude mice. In this study, fibulin-1 protein expression in breast carcinoma specimens and normal breast tissue was evaluated immunohistologically. Fibulin-1 protein expression was also semiquantitatively assessed by immunoblot analysis in a collection of normal breast tissues (n ¼ 18), benign tumours (n ¼ 5) and breast carcinomas (n ¼ 39)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 30 publications
1
50
0
1
Order By: Relevance
“…The two isoforms share a common 566-amino-acid N-terminal segment and differ in their C-termini. However, it (Greene et al, 2003). A further mechanism might be the imbalance in expression between Fbln-1 isoforms, a possibility supported by the finding of an increased Fbln-1C : Fbln-1D mRNA ratio observed in ovarian cancer cells compared to normal ovaries and benign tumours (Moll et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The two isoforms share a common 566-amino-acid N-terminal segment and differ in their C-termini. However, it (Greene et al, 2003). A further mechanism might be the imbalance in expression between Fbln-1 isoforms, a possibility supported by the finding of an increased Fbln-1C : Fbln-1D mRNA ratio observed in ovarian cancer cells compared to normal ovaries and benign tumours (Moll et al, 2002).…”
Section: Discussionmentioning
confidence: 55%
“…Several studies have implicated Fbln-1 as having a role in cancer (Qing et al, 1997;Twal et al, 2001;Du et al, 2002;Moll et al, 2002;Greene et al, 2003). An elevated expression of Fbln-1 is associated with human breast tumours (Forti et al, 2002;Greene et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its overexpression can serve as a tool for early detection of breast cancer and acts to promote breast cancer cell survival during doxorubicin treatment (Pupa et al, 2007). In a series of 36 primary breast carcinomas, the expression of mature fibulin-1 polypeptide (100 kDa) did not correlate with estrogen receptor-alpha (ERα) or progesterone receptor (PR) levels, whereas a positive correlation was found between fibulin-1 processing (50 kDa fragment) and ERα and PR protein levels (Greene et al, 2003). Castagnoli L, et al Atlas Genet Cytogenet Oncol Haematol.…”
Section: Breast Cancermentioning
confidence: 99%
“…Several studies have reported that fibulin-1 is overexpressed in various human neoplasias and it is implicated in processes such as invasion, motility, and in vivo tumor growth (Du et al, 2002;Greene et al, 2003;Moll et al, 2002;Qing et al, 1997;Twal et al, 2001). Fibulin-1 inhibits in vitro adhesion and motility of various carcinoma cell lines (Twal et al, 2001).…”
Section: ) Epithelial Cancers Various Cancersmentioning
confidence: 99%